INTEGRATION OF LOCAL CULTURAL VALUES IN INCLUSIVE EDUCATION: A CASE STUDY AT SD ALAM INSAN CENDEKIA BONDOWOSO - Ikrom Karyodiputro, Muhammad (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to explore the integration of local cultural values into inclusive education practices at SD Alam Insan Cendekia Bondowoso. Using a qualitative approach and a single case study design, data were collected through participant observation, semi-structured interviews, and documentation. Analysis was conducted using the Miles and Huberman interactive model with triangulation of sources, techniques, and time. The results indicate four main patterns of cultural integration: the application of mutual cooperation values in collaborative learning, the use of regional languages in interactions, the involvement of indigenous communities in the learning process, and the development of a contextual curriculum based on local culture. These results strengthen the framework for developing multicultural education that is responsive to culture and supports the achievement of SDG 4 on inclusive and quality education. The resulting integration model provides a practical framework for elementary school administrators in developing inclusive curricula that are responsive to cultural development while strengthening school partnerships with indigenous and social communities. This study contributes to the literature on multicultural and inclusive education based on local culture and can serve as a reference for policy and the development of comparative studies in various social and geographical contexts.